Pengaruh Substitusi Tepung Ikan Dengan Silase Cacing Tanah (Lumbricus rubellus) Dalam Pakan Buatan Terhadap Pemanfaatan Pakan Dan Pertumbuhan Juvenil Kerapu Macan (Epinephelus fuscogutattus) - Tanake, Gusti Ladini; Rachmawati, Diana; Subandiyono, Subandiyono (Journal of Aquaculture Management and Technology, 2013)
Tiger grouper is one of the important fishery commodities due to the market and highly economical value. One of the problems faced by the farmers was the high price of fish meal. Therefore, it was needed to find alternative ingredients as a substitution for the fish meal. One of the alternative was using earthworms (Lumbricus rubellus). This research aimed to determine the effects of substitution of fish meal with earthworm silage in the artificial food on the growth and survival rate of tiger grouper (Epinephelus fuscogutattus). This experiment used a completely randomized design (CRD) with 5 treatments and 3 replicates i.e. treatment A (0% without earthworm silage), B (25% earthworm silage), C (50% earthworm silage), D (75% earthworm silage), and E (100% earthworm silage). This research was carried out on April to June 2012 for 42 days in Great Hall of Brackish Water Aquaculture Development (BBPBAP), Jepara. The research revealed that the substitution of fish meal with earthworm silage resulted significant effect (P0,05) for EPP, PER, FCR, and SR values. It was suggested that diet with 100% substitution of earthworm silage, i.e. treatment E, could be used for tiger grouper feeds.